(untitled) (Journal of actual problems of jurisprudence, 2018)
This article describes current problems ofradiation safety.Particularattention is paid tothe analysis oflegislation acts of Kazakhstan and Russiain the field ofnuclear safetyand radiation security. The article deals withlegislationaimed at protecting thelife and healthof people andtheir environment. Key words: radiation and nuclear security, life and health of the people, environmental protection.